2020
DOI: 10.1002/apj.2552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ZnO nanoparticles loading in double‐layer polyvinylidene fluoride membrane for desalination via direct contact membrane distillation

Abstract: In this study, double‐layer flat sheet membranes consist of nanocomposite polyvinylidene fluoride (PVDF)–ZnO layer on the top, whereas pristine polymeric PVDF on the bottom was fabricated via the double‐casting phase inversion (DCPI) method. The nanocomposite layer was prepared by loading 0.5%, 1.0%, 1.5% and 2.0% of ZnO nanoparticles. The morphology of the membranes changed as ZnO nanoparticles were introduced in the top layer, where the structure is more rigid and porous than the bottom layer. The increment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…10,11,22 Besides, this agrees with another study, where the hydrophobic macromolecules can move to the air/polymer solution interface during the membrane casting and changes their chemical and physical properties. 11 Further analysis of the porosity of the membrane shows there was does not have significant changes when PVDF-HFP was blended in the top layer membrane, where 87% AE 0.02 and 88% AE 0.04, for membrane DB and D1 (from the previous study), 9 respectively. The blending ratio of PVDF-HFP in the membrane was suitable as compared to other studies reported by Wu et al, 11 where the blending of high PVDF-HFP content resulted in the less porous membrane.…”
Section: Membrane Hydrophobicitymentioning
confidence: 90%
See 4 more Smart Citations
“…10,11,22 Besides, this agrees with another study, where the hydrophobic macromolecules can move to the air/polymer solution interface during the membrane casting and changes their chemical and physical properties. 11 Further analysis of the porosity of the membrane shows there was does not have significant changes when PVDF-HFP was blended in the top layer membrane, where 87% AE 0.02 and 88% AE 0.04, for membrane DB and D1 (from the previous study), 9 respectively. The blending ratio of PVDF-HFP in the membrane was suitable as compared to other studies reported by Wu et al, 11 where the blending of high PVDF-HFP content resulted in the less porous membrane.…”
Section: Membrane Hydrophobicitymentioning
confidence: 90%
“…The membrane was fabricated following a modified double casting phase inversion (DCPI) method from the previous study as shown in Figure 2. 9 In this method, solution A was cast with a thickness of 350 μm, and solution B was cast with a gap clearance of 50 μm. The membrane was cast twice continuously, where a glass plate with cast solution A was not removed from the casting machine.…”
Section: Fabrication Of Double Layer Membranementioning
confidence: 99%
See 3 more Smart Citations